Domain-aware user model interoperability - Walsh, Edmond (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2013)
Exchanging user information between multiple sources can potentially bring many benefits that enhance the user experience in software applications. Richer and more dynamic user models can be constructed allowing more tailoring of content and services to the specific needs of each individual user. However, providing effective interoperability is a complex challenge as there can be significant heterogeneity between user models. As user model interoperability provides more expansive and detailed user models, it results in user models that contain information from multiple overlapping domains. Current generic approaches and tools offer insufficient support for the complex domain-specific nature of many user model interoperability tasks.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin.